ケインズ『貨幣論』：金融史理論としての再評価 - 小畑, 二郎; Obata, Jiro (立正大学経済学会, 2024)
この論文では，ケインズ『貨幣論』を金融史理論として再評価する．そして，『一般理論』へと発展する道筋を探求する．ケインズは，『貨幣論』において，貨幣経済の分析枠組みとしての基本方程式を，主として英米の金融史の理解に応用することを試みていた．『貨幣論』は，これまで『一般理論』のマクロ経済学によって吸収し尽くされた過去の著作として理解されてきたが，貨幣・金融の歴史理解のためには，むしろ『一般理論』よりも優れた視点も提供していた．それは，古代通貨の研究に始まり，国家貨幣と銀行貨幣という現代貨幣の二大分類に至る系譜を明らかにし，さらに投資の拡大によって促される投資金融経済の発展の原理を解明する著作として，理解することができる．そして，『一般理論』の理論革新の前提として，貨幣・資本理論の連続する革新過程をそこに読み取ることができる． この論文では，貨幣経済の変動を基本方程式に従って，①貨幣的要因，②投資要因，③産業要因という3 つの要因から究明するとともに，主として英米の金融史における「例証」を検討することによって，『一般理論』へと至るケインズの貨幣経済学の革新過程を理論的かつ歴史的に究明することを目指す．そして最後に，1929―32 年の世界恐慌に始まる大不況の教訓を生かして，現代のマクロ金融経済史の理論を作り上げていくための道筋を明らかにする． This essay presents a perspective for reading Keynes’s A Treatise on Money （Treatise） as the theory of financial history. Keynes introduced the Fundamental Equations (FEs) for the analysis of the monetary economy and applied them for understanding of the financial history. The causes of the fluctuation of the monetary economy are analyzed into three elements based on the FEs: monetary, investment and industrial elements. The first phase of credit cycle, recovery from the previous recession, begins with mild profit inflation promoted by excess investment over saving. The second phase, prosperity runs along the profit and commodity inflation with rising general price of commodity and increasing production and employment. The third phase of the cycle, recessions, goes on the process with declining general price. The recession turns to the recovery again with gradual rising general prices. It has been the credit cycle along the financial history since the 17th century. Historical illustration shows us the progress of the monetary economy since early prosperity of the merchant business by joint stock companies such as East India Company, Levant Company and Hudson Bay Company in the 17th Century. The excess investment over saving leads the profit inflation toward This essay presents a perspective for reading Keynes’s A Treatise on Money （Treatise） as the theory of financial history. Keynes introduced the Fundamental Equations (FEs) for the analysis ...